Rapidly involuting congenital hemangioma associated with smooth muscle hamartoma - A new didymosis? - Garofalo, L. (European Journal of Pediatric Dermatology, 2010)
A full-term baby was first observed in the fifth day of life for a swelling of the upper-right limb. Physical examination (Fig. 1) showed a 3 cm in size, bluish, hemispherical nodule of soft-elastic consistency, non tender on palpation. Immediately below and behind the nodule there was a hypertrichotic area of about 5 cm in diameter with blurred outlines. On palpation of this area there was a feeling of transient hardening and wrinkling. These findings led to the diagnosis of congenital hemangioma associated with smooth muscle hamartoma (hamartoma of the erector pili muscle). It was decided to monitor the two lesions clinically. After six months, the angiomatous lesion was significantly reduced, confirming the diagnosis of rapidly involuting congenital hemangioma, whereas the smooth muscle hamartoma remained unchanged.